2001
DOI: 10.1385/ep:12:3:351
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Insulinoma with Hepatoid Differentiation: A Unique Case with Alpha-Fetoprotein Production

Abstract: Hepatoid carcinomas are uncommon extra-hepatic neoplasms exhibiting features of hepatocellular carcinoma and they are most frequently described in the stomach. We report a 64-year-old woman with a malignant insulinoma showing focal hepatoid differentiation and biochemical evidence of alpha-fetoprotein (AFP) production. The current case is the first malignant insulinoma with hepatoid differentiation. Resection of the primary tumor followed by regional embolization was peformed. The patient died 22 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 11 publications
3
30
1
Order By: Relevance
“…This is typical of HCC with noninsulinoma hypoglycemia, 9 but is occasionally observed in patients with malignant insulinomas. 13,14 Yet, in most patients with metastatic insulinoma, we did not observe similar elevations of AFP, thus the predicative value of AFP level is low. Elevations of human chorionic gonadotropin or its ␣ or ␤ subunits sometimes occur but have not proved to be a consistent indication of malignancy.…”
Section: Discussioncontrasting
confidence: 54%
“…This is typical of HCC with noninsulinoma hypoglycemia, 9 but is occasionally observed in patients with malignant insulinomas. 13,14 Yet, in most patients with metastatic insulinoma, we did not observe similar elevations of AFP, thus the predicative value of AFP level is low. Elevations of human chorionic gonadotropin or its ␣ or ␤ subunits sometimes occur but have not proved to be a consistent indication of malignancy.…”
Section: Discussioncontrasting
confidence: 54%
“…Of particular interest, 2 patients (9.1%) complained of clinical symptoms referable to a concomitant pancreatic neuroendocrine tumor (1 insulinoma and 1 glucagonoma, respectively), underlining the possible association of pancreatic HC with other pancreatic neoplasms. Elevated AFP serum levels might be present at time of diagnosis in all HCs, despite tumor primary site [7,8,11,12,28,29,30,31,32,33,34]. Our review of pancreatic forms indeed reports a rate of 54.5% (12 out of 22 cases), bearing in mind that 3 papers did not report or did not assess AFP levels of their cases.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 71%
“…The admixed were as follows: 4 cases with neuroendocrine carcinoma [25,26,30,45], 1 case associated with malignant glucagonoma [33], 1 with malignant insulinoma [28], 1 case with acinar [36] and 4 with ductal adenocarcinoma [33]. Cuilliere et al [46] documented the only reported case of a benign hepatocellular neoplasm arising in the pancreas, which was an encapsulated solid adenoma in the pancreas that showed exclusively hepatocellular differentiation.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…In the literature, one case with malignant glucagonoma, one with malignant insulinoma, and three with neuroendocrine carcinoma have been reported. (2,3,(13)(14)(15) The neuroendocrine components in these cases were all intermingled intimately with hepatoid areas. In contrast, our case contained two separate lesions exhibiting different morphological and immunohistochemical profiles.…”
Section: Discussionmentioning
confidence: 89%